A fictitious pile method for interaction factor of two laterally loaded piles in multilayered isotropic soils. (December 2022) - Cao, Ming; Chen, Shengli
Abstract: An efficient fictitious pile method based on elasticity theory is presented for the analysis of interaction factor of two laterally loaded piles embedded in non-homogeneous soils. The problem is decomposed into two systems, namely the two fictitious piles acted upon by (partial) external loading, and an extended multilayered soil continuum acted upon by a system of pile-soil interaction forces at imaginary positions of the piles. The behavior/responses of the multilayered isotropic soils are analyzed through a computationally effective transfer matrix solution procedure. A Fredholm integral equation of the second kind is then deduced for the load-deformation relationship of a two-pile group system, by considering the equilibrium of the pile-soil interaction forces and the displacement compatibility between the fictitious pile and the extended soil. Comparison of the results calculated by the present fictitious pile method for displacement interaction factor between two piles embedded in multilayered isotropic soils has shown good agreement with the previous ones obtained by using the more rigorous finite element approach. The parametric numerical study demonstrates that the soft-over-stiff-over-soft soil layers have a profound effect on the pile-to-pile displacement interaction factor for the case of moment loading, which should be carefully considered in the practical design.